PENINGKATAN KETAHANAN PANGAN KELUARGA MELALUI MODIFIKASI SEMPOL TAHU WORTEL (SEMPOTEL) DI DESA AIR ASAM - Chessy Sripratiwi; Summayya Salsabilla Putri; Amanda Dewi Pricilia; Aqilah Najiani Afifah; Aulia Rahma; Clarissa Naurah Salsabillah; Disky Oktariani; Helen Novita; Fetri Vera Girsang; Rahmat Fauzan; Siti Khoirunnisa; Siti Nur Humairah; Syahirah Rizki Anila (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2025)
Family food security is one of the determining factors for quality of life, especially for people in rural areas. The “Locally Nutritious for Us (LOKALITA)” program in Air Asam Village was implemented as an effort to improve the knowledge and skills of housewives in processing local food ingredients into healthy snacks through the creation of